The role of pyroptosis in inflammatory diseases - Chai, Rong; Li, Ying; Shui, Linna; Ni, Longxing; Zhang, Ansheng (Frontiers in Cell and Developmental Biology, 2023)
Programmed cell death has crucial roles in the physiological maturation of an organism, the maintenance of metabolism, and disease progression. Pyroptosis, a form of programmed cell death which has recently received much attention, is closely related to inflammation and occurs via canonical, non-canonical, caspase-3-dependent, and unclassified pathways. The pore-forming gasdermin proteins mediate pyroptosis by promoting cell lysis, contributing to the outflow of large amounts of inflammatory cytokines and cellular contents. Although the inflammatory re-sponse is critical for the body’s defense against pathogens, uncontrolled inflammation can cause tissue damage and is a vital factor in the occurrence and progression of various diseases. In this review, we briefly summarize the major signaling pathways of pyroptosis and discuss current research on the pathological function of pyroptosis in autoinflammatory diseases and sterile in-flammatory diseases.